Spirituality and Religiosity in Adolescents Living With Sickle Cell Disease. (June 2016) - Clayton-Jones, Dora; Haglund, Kristin; Belknap, Ruth Ann; Schaefer, Jame; Thompson, Alexis A.
This study purports to address paucity in the literature regarding how adolescents with sickle cell disease (SCD) describe and experience spirituality and religiosity (S/R). This was a qualitative descriptive study. Two semi-structured interviews were conducted with nine adolescents ( M age = 16.2 years). Data were analyzed using a template analysis style and a concurrent analysis process of data reduction. Three major themes encompassed the participants' descriptions of the relationships between S/R, health and illness in their lives including S/R as sources for coping, influence of S/R beliefs on health and illness, and sharing S/R with Health Care Providers (HCPs). S/R as coping mechanisms included six threads: interconnecting with God, interconnecting with others, interconnecting with creative arts, scriptural metanarratives, transcendent experiences, and acceptance and finding meaning. Expectations of health providers included two threads: Religiosity is private/personal and sharing spiritual and religious beliefs is risky. S/R are particularly salient for adolescents with SCD.